PEMBACAAN HADIS DALAM PERSPEKTIF ANTROPOLOGI - Suryadilaga, Muhammad Alfatih (ALQALAM, 2014)
The article explains, at least three important problems, related to how to read hadis through the viewpoint of anthropology as a humanical science, why do it must be solved, and then what are the implications of it, in understanding some hadis. It becomes important to be discussed because, however, Muslims’ religiosity often touch humanity and social dynamic sides, constantly change and evolve. Its aim is clear, to ensure that hadis as second Muslims’ life guide after the Qur'an shalih li kulli zaman wa makan. Then, by using descriptive-analysis research method and focusing on the study of hadis that explain some procedures of  prayer, this can be concluded that, if we read through anthropological approach, the hadis are historical temporal valued. This means that it requires understanding and embodiment that must be adapted to the conditions of human in everytime. For example, the shape of mosque since the Prophet to present time has undergone many changes. So the forms or procedures of worship associated with that adjust for these changes, such as role of shaf in prayer, sutrah use, doing prayer on the vehicle, terrain, boats, up to recommend Muslimah to pray in jama’ah in the mosque, and so on.Keywords: hadis, anthropology, mosque, forms or procedures of worship